NON EXCLUSIVE BREAST FEEDING AT INFANCY, SOURCE OF UNACCEPTABLE BEHAVIOUR AMONG ADOLESCENTS, PERCEPTION OF EKITI STATE RESIDENT NIGERIAN NUTRITIONISTS - A.G., Aladegbola; Osakinle, E.O. (European Scientific Journal, ESJ, 2013)
This study is concerned with finding out the perception of Ekiti State Resident Nutritionists towards non exclusive breast feeding at infancy as the source of unacceptable behaviour. 250 nutritionists selected from Ekiti Central Senatorial District of Ekiti State constituted the sample for the study. A self designed questionnaire entitled ‘non exclusive breast feeding and unacceptable behaviour (NEBUB)’ was used to collect data for the study. The three hypotheses raised and tested using t-test statistics were accepted in their null forms. Findings from the study revealed that the perception of Ekiti State resident nutritionists towards non exclusive breast feeding at infancy as the source of unacceptable behaviour is negative. Both male and female nutritionists were not different in their perceptions. Ekiti State resident Nutritionists in the private operations were also not different from their colleagues in the government establishments in their perceptions towards non exclusive breast feeding as the cause of unacceptable behaviour in adolescents. Also, the educational background of the nutritionists did not cause any difference in their perceptions towards non exclusive breast feeding as the cause of unacceptable behaviour in adolescents. It was recommended that though exclusive breastfeeding is encouraged for the well being of an infant and indeed the most balanced diet in their early years, it has no valuable influence in their moral development across puberty and adolescence stages of development. It was suggested that other factors that could be responsible for unacceptable behaviour among adolescents should be investigated.